Maternal caries experience influences offspring’s early childhood caries – a birth cohort study. - Hariyani, N.; Do, Loc; Spencer, A.J.; Thomson, W.M.; Scott, Jane; Ha, D. (Wiley-Blackwell, 2020)
Objective: To describe early childhood caries (ECC) patterns and evaluate the associations with maternal caries experience and other factors.